ChemInform Abstract: One‐Pot Synthesis of (‐)‐Oseltamivir and Mechanistic Insights into the Organocatalyzed Michael Reaction. Issue 22 (3rd June 2014) - Mukaiyama, Takasuke; Ishikawa, Hayato; Koshino, Hiroyuki; Hayashi, Yujiro
Abstract The synthesis of title compound (I) is achieved via the asymmetric Michael reaction of pentanyloxyacetaldehyde with nitroethenylacetamide as the key step in seven steps and 36% overall yield.